2022
DOI: 10.3390/biomedicines10030702
|View full text |Cite
|
Sign up to set email alerts
|

Association between COVID-19 Diagnosis and Coronary Artery Thrombosis: A Narrative Review

Abstract: Coronavirus disease 2019 is characterized by its severe respiratory effects. Data early on indicated an increased risk of mortality in patients with cardiovascular comorbidities. Early reports highlighted the multisystem inflammatory syndrome, cytokine storm, and thromboembolic events as part of the disease processes. The aim of this review is to assess the association between COVID-19 and its thrombotic complications, specifically related to the cardiovascular system. The role of neutrophil extracellular trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 185 publications
1
19
0
Order By: Relevance
“…This nding is similar to the previous study which revealed that a higher neutrophil count in COVID-19 patients was found to be associated with a higher mortality rate among PLWH with SARS-CoV-2 infection [40]. This could be explained by emergency release of granulocyte colony-stimulating factor with activation of immature neutrophils, neutrophil maturation, neutrophil degranulation and release of neutrophil extracellular traps (NETs) [41,42]. Neutrophil activation and degranulation result in release of neutrophil-activation markers including resistin, lipocalin-2, hepatocyte growth factor and interleukin-8 which causes signi cant collateral damage.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This nding is similar to the previous study which revealed that a higher neutrophil count in COVID-19 patients was found to be associated with a higher mortality rate among PLWH with SARS-CoV-2 infection [40]. This could be explained by emergency release of granulocyte colony-stimulating factor with activation of immature neutrophils, neutrophil maturation, neutrophil degranulation and release of neutrophil extracellular traps (NETs) [41,42]. Neutrophil activation and degranulation result in release of neutrophil-activation markers including resistin, lipocalin-2, hepatocyte growth factor and interleukin-8 which causes signi cant collateral damage.…”
Section: Discussionsupporting
confidence: 90%
“…Neutrophil activation and degranulation result in release of neutrophil-activation markers including resistin, lipocalin-2, hepatocyte growth factor and interleukin-8 which causes signi cant collateral damage. The immune response of natural killer cells and T lymphocytes contributes to the formation of NETs and the activation of the complement system (C5 and C3) [42]. The result is the development of microvascular thrombosis, which leads to organ damage with an increased risk of severe COVID-19 and mortality [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with COVID-19, elevated levels of fibrinogen, von Willebrand factor, and D-dimer, indicate a hypercoagulative state, positively correlated with the severity of the disease [18] , [34] . Recent findings suggest that, in thrombi, the association between platelets and neutrophils stimulates the latter to form extracellular traps (NETs), which increase the tendency for platelet aggregation and negatively affect the prognosis of patients after SARS-CoV-2 infection [33] , [35] , [36] . At autopsy, the heart tissue of individuals who had COVID-19 exhibited vascular inflammation and extensive thrombosis both in the microcirculation and in the coronary arteries [26] , [37] .…”
Section: Molecular Mechanisms Of Sars-cov-2-induced Cardiac Microvasc...mentioning
confidence: 99%
“…Although severe inflammation is one of the known mechanisms of endothelial activation [35] , Johnson et al have recently found no evidence of cytokine-mediated activation, nor the expression of adhesion proteins such as intercellular adhesion molecule-1 (ICAM-1) and vascular adhesion molecule-1 (VCAM-1) in heart tissue [38] . Furthermore, in an in vitro study, exposure of ECs culture from the coronary artery to the viral nucleocapsid protein stimulates the expression of ICAM-1 and VCAM-1 [39] .…”
Section: Molecular Mechanisms Of Sars-cov-2-induced Cardiac Microvasc...mentioning
confidence: 99%